Routine non-thyroid head and neck cytology in a large UK centre: clinical utility and pitfalls. Issue 7 (8th July 2015) - Kaye, P V; Pigera, M; Khan, M M; Hollows, P; Beasley, N
Abstract Objective: This study aimed to examine the performance of head and neck cytology at Nottingham University Hospitals between 2009 and 2010. Methods: Cases were extracted from the Winpath pathology reporting system and correlations were investigated between results and the histological and clinical outcomes. Specimen adequacy and the sensitivity, specificity, positive and negative predictive values, and diagnostic accuracy of the cytology tests were calculated. Results: In all, 19.7 per cent of aspirates were judged to be inadequate. The absolute and relative sensitivities of head and neck cytology were 87.0 per cent and 89.0 per cent, respectively, and the absolute and relative specificities were 99.0 per cent and 97.0 per cent, respectively. The positive predictive values were 99.0 per cent and 96.0 per cent and the negative predictive values were 92.0 per cent and 92.0 per cent for a diagnostic accuracy of 94.5 per cent and 93.0 per cent. The performance was consistent with previous reports and superior to that of a recent UK series. The high rate of inadequate samples is, however, a concern. Conclusion: Head and neck cytology is a robust technique at our institution, although there are certain problem areas. There is room for improvement in the technical quality of fine needle aspiration.